Physical and Organoleptic Quality of Mayonnaise With Different Acidifying Ingredients (Pascasarjana Universitas Sulawesi Tenggara, 2022)
This study aims to determine the appropriate acidifying materials between vinegar, lime and pineapple in order to produce mayonnaise with good quality in terms of physical quality (pH and emulsion stability) and organoleptic (taste, aroma and color). The results showed that the use of different acidifying materials vinegar, lime and pineapple, showed significant differences in the physical quality of mayonnaise, both pH and emulsion stability and had no effect on organoleptic tests in this case the taste, aroma and color of mayonnaise. The use of different acidifying materials did not show a significant difference. For the physical quality of mayonnaise, the best treatment was obtained by using lime